Navigation in the user experience - Montegú , Cristián; José; Rosario; Renate; Felipe (Base Diseño e Innovación, 2014)
This article discusses the process and design methodologies of a navigation project based on insights of cognitive psychology. Through this navigation project for clínica las condes, we presented the graphic strategy and user experience to solve the problematic of navigation in a campus built from organic infrastructures of different architectures and times. The proposal is addressed from the navigation strategy up to the design of the different pieces needed for the correct space orientation.